Erratum: Asymmetric reduction of acetophenones with NaBH4 in the presence of mono-6-(1-methyl-3-imidazolium)-6-deoxy-β-cyclodextrin tosylate (Journal of Inclusion Phenomena and Macrocyclic Chemistry (2005) 56 (291) DOI: 10.1007/s10847-005-9018-5) - Tang, W. (2014)
10.1007/s10847-005-9018-5